P06 Correlates of level and loss of grip strength in later life: findings from the english longitudinal study of ageing and the hertfordshire cohort study. (2nd September 2017) - Westbury, LD; Syddall, HE; Dennison, EM; Cooper, C; Gale, CR
Abstract : Background: Low grip strength in later life is a risk factor for subsequent disability and mortality and a key component of sarcopenia. Established determinants of low grip strength level include: older age; shorter stature; poor nutrition; low physical activity; socio-economic disadvantage and multimorbidity. However, little is known about risk factors for accelerated loss of grip strength in later life. Methods: We examined socio-demographic, lifestyle and clinical predictors of baseline level and 8 year loss of grip strength in 3703 men and women (aged 52–82 years at baseline) in the English Longitudinal Study of Ageing (ELSA). Data on 441 men and women (aged 59–71 years at baseline) who participated in a 10 year follow-up of the Hertfordshire Cohort Study (HCS) were used for replication. Change in grip strength from baseline to the end of follow-up was characterised using linear mixed-effects models in ELSA as grip strength was measured at three time-points. A residual change method was used in HCS to obtain a measure of change in grip strength between two time-points which was independent of baseline level. Linear regression models adjusted for age and gender, as well as mutually-adjusted models, were used to examine the relationship between baseline predictors and level and change in grip strength in both cohorts. Results: Men in ELSA and HCS had higher average levels of grip strength at baseline, and accelerated rates of loss, compared with women. In ELSA, older age, shorter stature, and increased morbidity were associated with lower level, and accelerated rate of loss, of grip strength in both sexes. For example, accelerated loss of 0.04 (95%CI: 0.00, 0.08) standard deviation (SD) scores per additional morbidity were estimated from mutually-adjusted models; corresponding SD scores per SD decrease in height were 0.06 (95%CI: 0.03, 0.09). In mutually-adjusted analyses, socioeconomic disadvantage, low level of physical activity and poorer self-reported health were also associated with low grip strength level, but not with rate of loss. Analysis in HCS yielded similar results. Conclusion: Our results identify multimorbidity as a modifiable determinant of both level and loss of muscle strength in later life. The association between shorter stature and accelerated loss of grip strength suggests that developmental influences may also impact on rate of loss, as well as on level, of muscle strength in older age. This research will inform the development of lifecourse interventions to promote maintenance, and reduce loss, of muscle strength in later life.